An Investigation of Financial Spending and Distributive Justice Principles in NCAA Division I Athletic Departments. Issue 1 (April 2014) - Cooper, Coyte G.; Gaynor, Danielle; Shields, Edgar W.; Osborne, Barbara
<x content-type="archive" xml:space="preserve">Abstract</x> The Knight Commission cites two critical spending issues in Division I college athletics: the imbalance of rapidly rising expenditures against slow-moving revenues and the widening gap between wealthy conferences and struggling conferences (2009). The purpose of this study is to compare expenditure trends in men's revenue sports, men's non-revenue sports, and female sports from 2006–2009, to determine if differences in distributive justice principles exist in budget decisions of athletic departments that fall within three Division I classifications: Football Bowl Subdivision (FBS), Football Championship Subdivision (FCS), and the Non-Football Subdivision (Division I without Football). FBS institutions were found to almost completely abide by equity principles when making budgetary decisions while the FCS and Non-Football Subdivision made more decisions founded in principles of equality and need.